Benefit Sharing From Biodiversity to Human Genetics - Schroeder, Doris; Cook Lucas, Julie (Springer Netherlands : Imprint: Springer, 2013)
Biomedical research is increasingly carried out in low- and middle-income countries. International consensus has largely been achieved around the importance of valid consent and protecting research participants from harm. But what are the responsibilities of researchers and funders to share the benefits of their research with research participants and their communities? After setting out the legal, ethical and conceptual frameworks for benefit sharing, this collection analyses seven historical cases to identify the ethical and policy challenges that arise in relation to benefit sharing. A series of recommendations address possible ways forward to achieve justice for research participants in low- and middle-income countries.   Benefit sharing is a highly important topic and this publication is a welcome contribution to an under-researched field. Doris Schroeder is one of the world's leading bio-ethicists and has an outstanding reputation in the area of benefit sharing and ethics. Many of the other authors are also of excellent standing. The book is invaluable in bringing together a body of knowledge, theory and practice that has hitherto been fragmented and patchy.   Rachel Wynberg, Professor and Deputy Director, Environmental Evaluation Unit, University of Cape Town, South Africa   Benefit sharing is becoming a salient issue in the fields of bioethics, medical research, development, and the patenting of genes. This book will provide useful insights helping to design more effective benefit sharing regimes. I am deeply impressed by the book's comprehensiveness and the interesting and remarkable range of contributors.   Graham Dutfield, Professor of International Governance, University of Leeds, UK and author of Intellectual Property Rights and the Life Science Industries   Doris Schroeder's work has played an unmatched role in setting the international benefit-sharing agenda. In this impressive collection, which analyses examples of innovative benefit-sharing practice and provides a wide-ranging critical analysis of current thinking on benefit sharing, Doris Schroeder and Julie Cook Lucas offer an acute and perceptive assessment of the major and pressing challenges that need to be addressed in this area.   Michael Parker, Professor of Bioethics and Director of the Ethox Centre, University of Oxford, UK    .